Finite element simulation of compression tests on cellular metals - Oliveira, Branca F. de; Cunda, Luiz A. B. da; Creus, G. J.; Oschner, Andreas (2007)

(untitled)
Metal foams are materials of recent development and application that show interesting combinations of physical and mechanical properties. Many applications are envisaged for such materials, particularly in equipments of passive safety, because their high capacity of energy absorption under impact conditions. The damage analysis in metallic foams is a complex problem and must be performed in a finite strain context. Considering that compression is the dominant loading in impact situations, in this work a finite deformation simulation including damage effects of a compression test on a cellular metal sample is shown. A comparison with experimental results is also presented.